SIMILARITIES FROM THE NOVEL "BONU" BY IQBOL MIRZO - Tursunova Navruzaxon (Galaxy International Interdisciplinary Research Journal, 2022)
This article talks about the types of similes. The similes in Iqbal Mirza’s novel “Bonu” are explained. Excerpts from the work are cited and analyzed. Linguistic terms are used.